Table_S2-4 - Romaniuk, Andrzej; Shepherd, Alexandra; Clarke, David; Sheridan, Alison; Fraser, Sheena; Bartosiewicz, László; Herman, Jeremy S. (Dryad Digital Repository, 2016)
Table S2 - Summary measurements of Orkney vole skeletal elements. Table S3 - Rodent skeletal element relative frequencies and long bone fragmentation. Table S4 - Skeletal fragmentation in contexts from each trench.